2013
DOI: 10.3892/ol.2013.1725
|View full text |Cite
|
Sign up to set email alerts
|

miR-101 sensitizes A549 NSCLC cell line to CDDP by activating caspase 3-dependent apoptosis

Abstract: MicroRNA-101 (miR-101) is evidently downregulated in several types of cancer, including non-small cell lung cancer (NSCLC), and is crucial in sensitizing cells to chemotherapy drugs. The aim of the present study was to investigate the correlation between miR-101 and chemosensitivity in the A549 NSCLC cell line. Here, we used the human A549 cell line for transfection with an miR-101 overexpressing vector and detected the cytotoxic acticity, proliferation and apoptosis of cis-diaminedichloroplatinum (CDDP) in A5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 26 publications
(28 reference statements)
4
17
0
Order By: Relevance
“…Wang et al [131] reported that up-regulation of miR-138 gave rise to increased cell apoptosis and chemosensitivity of cisplatin-resistant A549 cells through down-regulation of the excision repair cross-complementation group 1 (ERCC1). In a recent study, Yin et al [133] demonstrated that over-expression of miR-101 sensitized A549 cells to cisplatin via the activation of caspase-3-dependent apoptosis. In a recent study, Yin et al [133] demonstrated that over-expression of miR-101 sensitized A549 cells to cisplatin via the activation of caspase-3-dependent apoptosis.…”
Section: Chemotherapymentioning
confidence: 99%
“…Wang et al [131] reported that up-regulation of miR-138 gave rise to increased cell apoptosis and chemosensitivity of cisplatin-resistant A549 cells through down-regulation of the excision repair cross-complementation group 1 (ERCC1). In a recent study, Yin et al [133] demonstrated that over-expression of miR-101 sensitized A549 cells to cisplatin via the activation of caspase-3-dependent apoptosis. In a recent study, Yin et al [133] demonstrated that over-expression of miR-101 sensitized A549 cells to cisplatin via the activation of caspase-3-dependent apoptosis.…”
Section: Chemotherapymentioning
confidence: 99%
“…miR-101 is a miRNA that regulates a variety of tumor-related biological processes by modulating the expression of several target genes at the transcript or protein level (25,26). Normally, miR-101 inhibits the expression of lung cancer promoting genes (17,27). In this study, we observed a miR-101 binding site at 3891–3912 nt of the DNMT3A 3′-UTR.…”
Section: Discussionmentioning
confidence: 99%
“…Loss and gain of miRNA functions contribute to the development of cancer through the upregulation of oncogenes and silencing of TSGs. miR-101 acts as a tumor suppressor, which regulates growth, apoptosis, migration and invasion of various tumor cells (1517). However, miR-101 has not been clearly identified as a selective regulator of DNMT3A in NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…miR-101 has been demonstrated to participate in the regulation of various cancers (11,12). For example, miR-101 was demonstrated to be a potent inhibitor of autophagy in breast cancer cells and the inhibition of miR-101 sensitized breast cancer cells to drug-mediated cell death (10).…”
Section: Introductionmentioning
confidence: 99%